Green Accounting in Sustainable Business Strategies: An Empirical Study of Environmentally Friendly Startups in Indonesia - Ela Widasari; Muhammad Hasyim Ashari; Umarudin Kurniawan (Oikonomia : Journal of Management Economics and Accounting, 2025)
Abstract This study aims to explore the meaning and implementation of green accounting in sustainable business strategies for eco-friendly startups in Indonesia. Increasingly pressing environmental issues are driving businesses, including startups, to integrate sustainability principles into their operations. Green accounting serves as a strategic instrument that enables structured recording, measuring, and reporting of environmental impacts. Using a qualitative phenomenological approach, this study explores the subjective experiences of startups who have implemented green accounting in various cities such as Jakarta, Bandung, Yogyakarta, and Bali. Data were obtained through in-depth interviews, observation, and documentation, then analyzed using the Colaizzi model. The results show that green accounting is understood not only as a reporting tool, but also as a manifestation of ethical values and ecological responsibility. However, its implementation still faces constraints such as limited resources, technical literacy, and regulations that are not yet optimally supportive. Nevertheless, opportunities for strengthening are open through digital technology, ESG-based funding, and multi-stakeholder collaboration. These findings confirm that green accounting plays a crucial role in green business transformation, while contributing to public policy, sustainable entrepreneurial practices, and the development of a more environmentally responsible startup ecosystem.